Cross-Cultural Measurement Invariance in the Personality Inventory for DSM-5✰. (October 2021) - Sorrel, M.A.; García, L.F.; Aluja, A.; Rolland, J.P.; Rossier, J.; Roskam, I.; Abad, F.J.
Highlights: It is again evidenced that the loading structure of the PID-5 is very complex. Partial scalar invariance was supported which allowed for factor means comparisons. The domain where the differences were greatest was psychoticism. The influence of non-invariant items found to be was minimal. Abstract: The validity of cross-cultural comparisons of test scores requires that scores have the same meaning across cultures, which is usually tested by checking the invariance of the measurement model across groups. In the last decade, a large number of studies were conducted to verify the equivalence across cultures of the dimensional Alternative Model of Personality Disorders (DSM-5 Section III). These studies have provided information on configural invariance (i.e., the facets that compose the domains are the same) and metric invariance (i.e., facet-domain relationships are equal across groups), but not on the stricter scalar invariance (i.e., the baseline levels of the facets are the same), which is a prerequisite for meaningfully comparing group means. The present study aims to address this gap. The Personality Inventory for DSM-5 (PID-5) was administered to five samples differing on country and language (Belgium, Catalonia, France, Spain, and Switzerland), with a total of 4, 380 participants. Configural and metric invariance were supported, denoting that the model structure was stable across samples. Partial scalar invariance was supported, being minimal the influence of non-invariant facets. This allowed cross-cultural mean comparisons. Results are discussed in light of the sample composition and a possible impact of culture on development of psychopathology.